Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1118/1.598383
|View full text |Cite
|
Sign up to set email alerts
|

Viability of an isocentric cobalt‐60 teletherapy unit for stereotactic radiosurgery

Abstract: This manuscript has been reproduced from the miadilm master. UMI films the text directly from the original or copy submiUed. Thus, m e thesis and dissertation copies are in typewriter face, while others may be from any type of computer printer.The quality of this mproductkn is dependent upon the quality of the copy submitted. Broken or indistinct print, cobred or poor quality illustrations and photographs, print Meedthrough, substandard margins, and improper alignment can adversely affect repmduction.In the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…An 80-20% penumbra distance of 4.5 mm was observed. Note that our results are consistent with the measured penumbra of cobalt sources reported in Adams and Warrington (2008), Poffenbarger and Podgorsak (1998), Raja Singh et al (2000) and Warrington and Adams (2002).…”
Section: Co Beamlet Analysissupporting
confidence: 93%
“…An 80-20% penumbra distance of 4.5 mm was observed. Note that our results are consistent with the measured penumbra of cobalt sources reported in Adams and Warrington (2008), Poffenbarger and Podgorsak (1998), Raja Singh et al (2000) and Warrington and Adams (2002).…”
Section: Co Beamlet Analysissupporting
confidence: 93%
“…There has been relatively little development in Co-60 units necessary for implementation of conventional 3DCRT and IMRT techniques. Reports on modifications of conventional Co-60 units for radiosurgery (Poffenbarger andPodgorsak 1998, Singh et al 2000) and the use of asymmetric jaws (van der Giessen 2001) have shown that beam characteristics (e.g. penumbra, flatness and beam output) of modified Co-60 units compare well with linacs.…”
Section: Introductionmentioning
confidence: 99%